Discovery of a new ligament of the lumbar spine: the midline interlaminar ligament - Simonds, Emily; Iwanaga, Joe; Ishak, Basem; Reina, Miguel Angel; Oskouian, Rod J.; Tubbs, R. Shane (The spine journal, 2020)
BACKGROUND: The ligaments of the lumbar spine are integral to structural integrity and have been well-studied. However, during the routine dissection of the lumbar spine, we identified to our knowledge, a previously undescribed midline ligament near the ligamenta flava but distinctly separate. PURPOSE: The purpose of this study was to investigate the morphology of this ligament termed by us the midline interlaminar ligament. STUDY DESIGN: Cadaveric study. METHODS: Thirty-four lumbar vertebral levels from 10 fresh frozen adult cadavers were dis- sected. The ligamenta flava were dissected anteriorly. The junction between the right and left liga- menta flava was observed and the presence and morphometrics of the median interlaminar ligament (MIL) were recorded. Random ligaments underwent tensile strength testing. Metal wires were also placed on the ligaments and fluoroscopy performed. RESULTS: Twenty-six out of 34 (76.5%) lumbar levels were found to have a MIL traveling on the internal aspect of the most medial aspect of the laminae and positioned slightly anterior to the plane of the ligamenta flava. The mean length and width of the MIL were 9.03 +/- 4.29 mm and 4.94 +/- 1.56 mm, respectively. The mean force necessary until failure for the MIL was 12.3N. CONCLUSIONS: Based on our findings, a distinct MIL was identified in the lumbar spine at the majority of lumbar levels. CLINICAL SIGNIFICANCE: The MIL might have clinical significance and potential biomechanical importance. Further studies are now necessary to better elucidate this anatomical structure.
Available online 9 December 2019
Gesehen am 15.04.2020